The Lamentations of the Disadvantaged: Reading Psalm 73 in the Context of Oppression in Contemporary Nigerian Society - Biwul, Joel Kamsen Tihitshak (Old Testament Essays, 2023)
The evil of humanity’s inhumanity to fellow humans via the act of oppression is pervasive across human societies. This evil will continue unabated because of the inherent evil inclination of the benefiting perpetrators. The lamentation in Ps 73 reveals the enigmatic irony of divine theodicy, an apparent contradiction of divine promise vis-à-vis prevailing orchestrated oppression in society. The empirical paradox of life unavoidably poses the question: “why should someone happily celebrate the plight of the disadvantaged ‘other,’ becoming emotionally insensitive, oppressing fellow humans against good conscience, simply because the oppressor is in position of privilege in society?” This is the aching question many oppressed Nigerians are constantly asking. This article comparatively resonates the emotional torture of the psalmist consequent upon the disadvantaged economic status vis-à-vis the oppressed economic, political, religious, social, and psychological condition of many Nigerians today. https://doi.org/10.17159/2312-3621/2022/v35n3a4